Trends in cigarette use and health insurance coverage among US adults with mental health and substance use disorders. (16th November 2022) - Creedon, Timothy B.; Wayne, Geoffrey Ferris; Progovac, Ana M.; Levy, Douglas E.; Cook, Benjamin Lê
Abstract: Aims: To estimate recent trends in cigarette use and health insurance coverage for United States adults with and without mental health and substance use disorders (MH/SUD). Design: Event study analysis of smoking and insurance coverage trends among US adults with and without MH/SUD using 2008–19 public use data from the National Survey on Drug Use and Health, an annual, cross‐sectional survey. Setting: USA. Participants: A nationally representative sample of non‐institutionalized respondents aged 18–64 years ( n  = 448 762). Measurements: Outcome variables were three measures of recent cigarette use and one measure of past‐year health insurance coverage. We compared outcomes between people with and without MH/SUD (MH disorder: past‐year mental illness, predicted from Kessler‐6 and the World Health Organization–Disability Assessment Schedule impairment scale; SUD: met survey‐based DSM‐IV criteria for past‐year alcohol, cannabis, cocaine or heroin use disorder) and over time. Findings: Comparing pooled data from 2008 to 2009 and from 2018 to 2019, current smoking rates of adults with MH/SUD decreased from 37.9 to 27.9% while current smoking rates of adults without MH/SUD decreased from 21.4 to 16.3%, a significant difference in decrease of 4.9 percentage points (pts) [95% confidence interval (CI) = 3.3–6.6 pts]. Daily smoking followed similar patterns (difference in decrease of 3.9 pts (95% CI = 2.3–5.4 pts). Recent smoking abstinence rates for adults with MH/SUD increased from 7.4 to 10.9%, while recent smoking abstinence rates for adults without MH/SUD increased from 9.6 to 12.0%, a difference in increase of 1.0 pts (95% CI = −3.0 to 0.9 pts). In 2018–19, 11% of net reductions in current smoking, 12% of net reductions in daily smoking and 12% of net increases in recent smoking abstinence coincided with greater gains in insurance coverage for adults with MH/SUD compared to those without MH/SUD. Conclusions: Improvements in smoking and abstinence outcomes for US adults with mental health and substance use disorders appear to be associated with increases in health insurance coverage.